Cellular and Molecular Immunology - Dr FATMI Ahlam (Université Mohamed Boudiaf - M’sila, 2026)
The aim of this course is to understand how the immune system develops through haematopoiesis in primary organs (bone marrow and the thymus) and functions via secondary organs (lymph nodes, spleen and MALT). Haematopoietic stem cells (HSCs) give rise to myeloid and lymphoid lineages under the influence of cytokines such as GM-CSF, G-CSF and IL-7. Lymphopoiesis produces B cells, T cells and NK cells, which are activated through the recognition of antigens, costimulation (CD28/CD80/CD86) and cytokine signalling (IL-2). Antibodies (IgG, IgM, IgA, IgE and IgD) produced by B cells mediate opsonisation, complement activation and ADCC, while cytotoxic T cells (CD4⁺ and CD8⁺) and NK cells release cytokines. T-B interactions in germinal centres drive antibody maturation through signal transduction (ITAMs, ZAP-70 and JAK-STAT). Long-term immune memory is essential for vaccination and can be enhanced by adjuvants. Hybridoma technology enables the production of monoclonal antibodies (murine, chimeric, humanised and fully human) for use in diagnostics and therapy. Immune tolerance is maintained by central and peripheral mechanisms involving molecules such as CTLA-4. Anti-infectious immunity combats viral, bacterial, fungal and protozoan pathogens, while immunopathology encompasses immunodeficiencies, autoimmunity, hypersensitivity (types I–IV) and cancer immunotherapy. Finally, transplantation involves identifying graft types and the mechanisms of rejection (hyperacute, acute and chronic), as well as immunosuppressive therapy.
Keywords: Hematopoiesis; immune response; cytokines; antibodies; effector functions; germinal centre reaction; memory; hybridomas; monoclonal antibodies; immunopathology.